Constraining the quenching mechanisms of galaxy clusters through the evolution of stellar mass functions within GOGREEN and GCLASS - Hewitt, Guillaume (University of Waterloo, 2024)
We present an analysis of the stellar mass functions (SMFs) of 17 rich galaxy clusters within the GOGREEN and GCLASS surveys in the redshift range of 0.8 < z < 1.5, down to a stellar mass limit of log(M/M⊙) = 9.5. We fit all the data simultaneously with a model that allows the Schechter function parameters of the quiescent and star-forming populations to vary smoothly with radius and redshift. The model also fits for the concentration parameter of each population, and the quenched fraction is modeled as a smooth function of redshift and velocity dispersion. We fit the data in a Bayesian manner, using MCMC. We find no significant dependence of the shape of the star-forming SMF on radius nor redshift, and find it to be consistent with the field. We confirm previous results of a radial dependence on the quenched fraction. We find a moderately significant radial dependence on the α and M* parameters of the quiescent population SMF. The cluster core has a highly elevated quenched fraction, yet the core quiescent SMF is more similar in shape to the quiescent field. The cluster non-core has an moderately elevated quenched fraction, and its quiescent SMF is more similar to the shape of the star-forming field. We explore the contributions of ‘early mass quenching’ and mass-independent ‘environmental quenching’ models in each of these radial regimes. We find the core to be described primarily by early mass quenching, which we interpret as accelerated quenching of massive galaxies in protoclusters, possibly through merger-driven AGN feedback, and the non-core to be described by environmental-quenching, signifying the increase of mass-independent quenching mechanisms that dominate low redshift clusters.
Keywords: galaxy evolution; galaxy clusters; galaxies; astrophysics